The cytoplasmic cage domain of the mechanosensitive channel MscS is a sensor of macromolecular crowding - Rowe, Ian (The Rockefeller University Press, 2014)
Cells actively regulate the macromolecular excluded volume of the cytoplasm to maintain the reciprocal fraction of free aqueous solution that is optimal for intracellular processes. However, the mechanisms whereby cells sense this critical parameter remain unclear. The mechanosensitive channel of small conductance (MscS channel), which is the major regulator of turgor in bacteria, mediates efflux of small osmolytes in response to increased membrane tension. At moderate sustained tensions produced by a decrease in external osmolarity, MscS undergoes slow adaptive inactivation; however, it inactivates abruptly in the presence of cytoplasmic crowding agents. To understand the mechanism underlying this rapid inactivation, we combined extrapolated and equilibrium molecular dynamics simulations with electrophysiological analyses of MscS mutants to explore possible transitions of MscS and generated models of the resting and inactivated states. Our models suggest that the coupling of the gate formed by TM3 helices to the peripheral TM1–TM2 pairs depends on the axial position of the core TM3 barrel relative to the TM1–TM2 shaft and the state of the associated hollow cytoplasmic domain (“cage”). They also indicate that the tension-driven inactivation transition separates the gate from the peripheral helices and promotes kinks in TM3s at G113 and that this conformation is stabilized by association of the TM3b segment with the β domain of the cage. We found that mutations destabilizing the TM3b–β interactions preclude inactivation and make the channel insensitive to crowding agents and voltage; mutations that strengthen this association result in a stable closed state and silent inactivation. Steered simulations showed that pressure exerted on the cage bottom in the inactivated state reduces the volume of the cage in the cytoplasm and at the same time increases the footprint of the transmembrane domain in the membrane, implying coupled sensitivity to both membrane tension and crowding pressure. The cage, therefore, provides feedback on the increasing crowding that disengages the gate and prevents excessive draining and condensation of the cytoplasm. We discuss the structural mechanics of cells surrounded by an elastic cell wall where this MscS-specific feedback mechanism may be necessary.